1998
DOI: 10.1093/carcin/19.11.1925
|View full text |Cite
|
Sign up to set email alerts
|

Allelic losses and DNA methylation at DNA mismatch repair loci in sporadic colorectal cancer

Abstract: Normal and tumor DNA samples of 35 patients with sporadic colorectal carcinoma were analyzed for microsatellite alterations at 12 markers linked to mismatch repair loci: hMLH1, hMSH2, hMSH3, hMSH6, hPMS1 and hPMS2. Remarkably, no correlation was observed between the replication error phenotype (RER+) and allelic losses at these loci. Hemizygous deletions, seen in 6/35 (17%) informative cases at hMLH1, 4/27 (15%) at hMSH2/hMSH6 and 6/34 (18%) at hMSH3, were rarely found in RER+ tumors. Since mismatch repair pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Whereas in SCC the frequency of allelic loss at MLH1 was higher (38%), which was comparable with that detected in breast cancer (46%; Benachenhou et al, 1999) and non-small cell lung cancer (43%; Wieland et al, 1996). The frequency of MSH2 allelic loss in TCC detected in this study (14%) was comparable to that detected in non-small cell cancer (11.5%; Benachenhou et al, 1998a) and also in sporadic colorectal cancer (15%; Benachenhou et al, 1998b). A higher frequency of allelic loss at MSH2 was detected in SCC of the bladder (38%).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Whereas in SCC the frequency of allelic loss at MLH1 was higher (38%), which was comparable with that detected in breast cancer (46%; Benachenhou et al, 1999) and non-small cell lung cancer (43%; Wieland et al, 1996). The frequency of MSH2 allelic loss in TCC detected in this study (14%) was comparable to that detected in non-small cell cancer (11.5%; Benachenhou et al, 1998a) and also in sporadic colorectal cancer (15%; Benachenhou et al, 1998b). A higher frequency of allelic loss at MSH2 was detected in SCC of the bladder (38%).…”
Section: Discussionsupporting
confidence: 79%
“…This second mutational step may be revealed as LOH, which was previously reported at the hMLH1 locus in HNPCC (Hemminki et al, 1994) as well as at hMLH1 and hMSH2 loci in sporadic colorectal cancers (Tomlinson et al, 1996;Benachenhou et al, 1998b), in non-small cell lung cancer (Benachenhou et al, 1998a) and in breast cancer (Benachenhou et al, 1999). Christensen et al (1998) reported the occurrence of LOH at microsatellites located close to hMSH2 and hMLH1 and suggested a possible role of these genes in causing profound MSI in bladder cancer.…”
Section: Discussionmentioning
confidence: 56%
“…We decided to use two alternative approaches (see below). Benachenhou et al, 1998). The cleavage at the six HpaII/MspI sites located within the 700 bp upstream of the GPC3 transcription initiation site was examined by the means of two PCR reactions (one for the two distal sites and one for the four proximal sites; Figure 1A).…”
Section: Methylation Assaysmentioning
confidence: 99%
“…Although our markers were already shown as sensitive to detecting RER in sporadic colorectal cancers (Benachenhou et al, 1998a), we additionally examined two markers GGAA4D07 and GGAA2E02 recently reported as unstable in 30% (11 out of 37) and 41% (15 out of 37) of breast cancer patients respectively (Paulson et al, 1996). These two markers did not reveal any instability in the 22 tumours examined here (data not shown).…”
Section: Microsatellite Instabilitymentioning
confidence: 99%